Enabling an atom-economic production of chiral amino alcohols by electrodialysis with bipolar membranes. Issue 7 (28th November 2019) - Gao, Wei-Ting; Chen, Qing; Du, Ming-Gu; Zhang, Wei-Ming; Cao, Chang-Yan; Song, Wei-Guo
Abstract : Along with catalytic hydrogenation, producing pure chiral amino alcohols with a perfect atom economy is achieved by electrodialysis with bipolar membranes. Abstract : Optically pure amino alcohols are widely used as essential building blocks of catalysts and auxiliaries in asymmetric synthesis, especially in pharmaceuticals. Catalytic hydrogenation has been regarded as the most effective route to produce chiral amino alcohols, but it is still unsatisfactory, which mainly manifests in the involvement of extra acids and bases, thus generating a large amount of inorganic salt byproducts, along with a relatively low yield. In this paper, we propose a novel approach that integrates catalytic hydrogenation and electrodialysis with bipolar membranes (EDBM) to produce pure chiral amino alcohols in a completely green way. EDBM tackles the sustainability issue by splitting the resulting salt of the hydrogenation into the corresponding acid and base (amino alcohol solutions), and the acid could be reused in the next batch directly and a closed loop forms. Here, as a model system to demonstrate the feasibility, a biorenewable chiral l -alanine solid and clean H2 gas are used as the feed stocks and finally converted into a pure l -alaninol product successfully, with no discharge of harmful substances. Furthermore, three typical mineral acids (H3 PO4, H2 SO4 and HCl) have been investigated systematically and achieved similar performances. The results of all tests and the cost analysis strongly suggest that this new approach is widely applicable, highly productive and sustainable. It demonstrates a true atomically economic route to produce chiral amino alcohols and entirely meets the requirements of green chemistry.